Newly Synthesized Fluorinated Cinnamylpiperazines Possessing Low In Vitro MAO-B Binding - Ivana I. Jevtić; Thu Hang Lai; Jelena Z. Penjišević; Sladjana Dukić-Stefanović; Deana B. Andrić; Peter Brust; Sladjana V. Kostić-Rajačić; Rodrigo Teodoro (Molecules, 2020)
Herein, we report on the synthesis and pharmacological evaluation of ten novel fluorinated cinnamylpiperazines as potential monoamine oxidase B (MAO-B) ligands. The designed derivatives consist of either cinnamyl or 2-fluorocinnamyl moieties connected to 2-fluoropyridylpiperazines. The three-step synthesis starting from commercially available piperazine afforded the final products in overall yields between 9% and 29%. An in vitro competitive binding assay using l-[3H]Deprenyl as radioligand was developed and the MAO-B binding affinities of the synthesized derivatives were assessed. Docking studies revealed that the compounds 8–17 were stabilized in both MAO-B entrance and substrate cavities, thus resembling the binding pose of l-Deprenyl. Although our results revealed that the novel fluorinated cinnamylpiperazines 8–17 do not possess sufficient MAO-B binding affinity to be eligible as positron emission tomography (PET) agents, the herein developed binding assay and the insights gained within our docking studies will certainly pave the way for further development of MAO-B ligands.